Interaction between Trichoderma asperellum and Bacillus spp. in the biological control of disease in the soya bean - Adeliane Ferreira Braga; Leonardo de Castro Santos; Suellen Polyana da Silva Cunha Mendes; Francielly Abrenhosa Pires; Alaerson Maia Geraldine; Weder Nunes Ferreira Junior (Revista Ciência Agronômica)
ABSTRACT One of the main phytosanitary problems in major crops are phytonematodes, which are characterised as difficult to control. In view of this, biocontrol, through the use of biological agents, has become a driving force in controlling these pathogens. The aim of this study was to evaluate the compatibility of microorganisms, and detect the possibility of antagonistic effects, influence on growth, or synergistic action when microorganisms are jointly applied to crops. Microbiological analyses were carried out to observe the interaction of the fungus Trichoderma asperellum with the bacteria Bacillus subtilis and Bacillus methylotrophicus. It was found that the interaction between the genera Bacillus and Trichoderma did not promote any increase in the fresh or dry weight of the roots or shoots of the soya plants; however, based on the results of the microbiological analysis of the fungi and bacteria, the interaction was found to be promising, particularly in the evaluation carried out on the seventh day. Considering the number of viable spores, the interaction between B. subtilis + T. asperellum showed better results than B. methylotrophicus + T. asperellum. The Interaction between the genera Bacillus and Trichoderma showed the potential for joint use in the biological control of the soya bean.